Ukraine, The EU and Russia History, Culture and International Relations - Velychenko, S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
This book surveys the Ukrainian-EU relationship in light of the legacies of more than two hundred years of direct Russian rule. It examines interrelationships between identities, loyalties and political/cultural orientations, reviews policies, and identifies salient forces and trends.
Keywords: Russia—Politics and government; Europe—Politics and government; European Union; Political science; International relations; Russian and Post-Soviet Politics; European Politics; European Union Politics; Political Science; International Relations